1994
DOI: 10.1002/pro.5560031122
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycine (residue 89) in the central helix of EF‐hand protein troponin‐C exposed following amino‐terminal α‐helix deletion

Abstract: Because an N-terminal a-helical (N-helix) arm and a KGK-triplet (residues "KGKgn) in the central helix of troponin-C (TnC) are missing in calmodulin, several recent studies have attempted to elucidate the structurefunction correlations of these units. Presently, with a family of genetically manipulated derivatives especially developed for this study and tested on permeabilized isolated single skeletal muscle fiber segments, we explored the specificities of the amino acid residues within the N-helix and the KGK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Using a second spectral probe mutant (Phe29Trp; Pearlstone et al, 1992) to measure calcium sensitivity via far and near-UV CD and¯uorescence techniques, these workers showed a reduction of calcium af®nity in the N domain of 1.6 to 1.8-fold and a reduced Ca 2 -activated enzymatic activity in reconstituted troponin-tropomyosinactomyosin S1 and myo®brillar ATPase systems . Similar conclusions have been drawn regarding the critical role of the Nterminal helix in the Ca 2 -mediated activity using a (residues 1 to 14) deletion mutant of avian TnC (Smith et al, 1994) and a (1 to 15) deletion mutant of rabbit skeletal TnC (Ding et al, 1994;Gulati et al, 1993). Our work provides a structural basis for these results.…”
Section: The N Helixmentioning
confidence: 51%
“…Using a second spectral probe mutant (Phe29Trp; Pearlstone et al, 1992) to measure calcium sensitivity via far and near-UV CD and¯uorescence techniques, these workers showed a reduction of calcium af®nity in the N domain of 1.6 to 1.8-fold and a reduced Ca 2 -activated enzymatic activity in reconstituted troponin-tropomyosinactomyosin S1 and myo®brillar ATPase systems . Similar conclusions have been drawn regarding the critical role of the Nterminal helix in the Ca 2 -mediated activity using a (residues 1 to 14) deletion mutant of avian TnC (Smith et al, 1994) and a (1 to 15) deletion mutant of rabbit skeletal TnC (Ding et al, 1994;Gulati et al, 1993). Our work provides a structural basis for these results.…”
Section: The N Helixmentioning
confidence: 51%
“…If the force level in the repeat cycle was within 1-2% of that in the first cycle, no further repletion was attempted. The final assurance regarding completion of the loading of the particular protein was derived from quantitative analyses of polyacrylamide gel electrophoresis (SDS-PAGE) developed from selected experimental fiber segments, as described previously (Ding et al. 1994).…”
Section: Methods (A) Experimental Proceduresmentioning
confidence: 99%
“…Mutational studies of the central helix in TnC have previously shown that both a required amount of flexibility and a critical length are necessary for optimal activity, suggesting that the linker region may function as a molecular ruler, maintaining a proper relationship between the N-and C-domains of cTnC (35)(36)(37). In the present study, we utilized 15 N R 2 values to measure flexibility within the linker region of cTnC in the presence of full-length cTnI.…”
Section: Discussionmentioning
confidence: 99%